A Note on Right Full k-Ideals of Seminearrings - Kornthorng, Nanthaporn; Iampan, Aiyared (Journal of Informatics and Mathematical Sciences, 2012)
This work extends the idea of k-ideals of semirings to seminearrings, the concept of k-ideals of seminearrings is introduced and investigated, which is an interesting for seminearrings and some interesting characterizations of k-ideals of seminearrings are obtained. Also, we prove that the set of all right full k-ideals of an additively inverse seminearring in which addition is commutative forms a complete lattice which is also modular in the same way as of the results of Sen and Adhikari.